Serum Pharmacochemistry and Network Pharmacology Reveal Active Compounds and Mechanisms of the Huaxian Formula in Alleviating Radiation-Induced Pulmonary Fibrosis - Gong C; Chen J; Zou P; Fang Z; Quan L; Wang J; Yin J; Lin B; Lang J; Chen M (Drug Design, Development and Therapy)
CuiCui Gong,1– 3 Junyang Chen,2 Pingjin Zou,2 Zengyi Fang,2 Li Quan,1– 3 Jing Wang,2,4 Jie Yin,2,5 Bing Lin,1 Jinyi Lang,1– 5 Meihua Chen2,3 1School of Clinical Medicine, Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan, 610032, People’s Republic of China; 2Department of Radiation Oncology, Radiation Oncology Key Laboratory of Sichuan Province, Sichuan Clinical Research Center for Cancer, Sichuan Cancer Hospital & Institute, Sichuan Cancer Center, University of Electronic Science and Technology of China, Chengdu, 610041, People’s Republic of China; 3Institute of Integrated Traditional Chinese and Western Medicine Cancer Research, Chengdu University of Traditional Chinese Medicine, Chengdu, 610032, People’s Republic of China; 4Department of Oncology, School of Clinical Medicine, Southwest Medical University, Luzhou, Sichuan, 646000, People’s Republic of China; 5School of Medicine, University of Electronic Science and Technology of China, Chengdu, Sichuan, 611731, People’s Republic of ChinaCorrespondence: Jinyi Lang, School of Clinical Medicine, Chengdu University of Traditional Chinese Medicine, Chengdu, 610032, People’s Republic of China, Email langjy610@163.com Meihua Chen, Department of Radiation Oncology, Radiation Oncology Key Laboratory of Sichuan Province, Sichuan Clinical Research Center for Cancer, Sichuan Cancer Hospital & Institute, Sichuan Cancer Center, University of Electronic Science and Technology of China, Chengdu, 610041, People’s Republic of China, Email chenmeihua@scszlyy.org.cnPurpose: Radiation-induced pulmonary fibrosis (RIPF) is a serious complication of radiotherapy that lacks effective treatment options. The Huaxian formula (HXF), a traditional Chinese herbal remedy, shows promise in alleviating RIPF; however, its active ingredients and underlying mechanisms remain poorly understood.Methods: Through serum pharmacochemistry, network pharmacology, molecular docking, and experimental validation, we investigate the potential mechanisms of HXF in the prevention and treatment of radiation-induced pulmonary fibrosis (RIPF).Results: Histological examination and non-invasive computed tomography (CT) scans in animal experiments revealed that HXF improved extracellular matrix collagen deposition in the lung tissue of irradiated mice and reduced fibrosis manifestations on CT images. Analysis of post-HXF administration serum samples identified 21 enriched compounds as potential active compounds, with 430 corresponding prospective targets. Overlapping these compounds with 991 RIPF-related genes yielded 127 genes primarily associated with the PI3K-Akt signaling pathway, EGFR tyrosine kinase inhibitor resistance, and the MAPK signaling pathway. Molecular docking indicated that key compounds in HXF serum, 5,7,8-trimethoxyflavone, and hyperoside, exhibited strong affinity with key targets. Finally, animal experiments confirmed that HXF significantly inhibited the expression of p-Akt and p-PI3K proteins in the lung tissue of irradiated mice.Conclusion: Our research results indicate that HXF may exert its effects on the prevention and treatment of radiation-induced pulmonary fibrosis (RIPF) through multiple pathways and targets, with the PI3K-Akt signaling pathway likely playing the most crucial role in this process. Keywords: radiation-induced pulmonary fibrosis, Huaxian formula, serum pharmacochemistry, network pharmacology, active compounds